Rancangan Sistem Kontrol dan Monitoring pada Wire Selection Boxes - Suciningtyas, Ika Karlina Laila Nur; Risandriya, Sumantri Kurniawan; Ismail, Aziz; Maulana, Rifky Daniel (Journal of Applied Electrical Engineering, 2024)
The issue of incorrect material usage in the industry's production process is a primary focus for quality control, as it directly impacts customers. This research was conducted due to challenges in maintaining the continuity of the manual cable selection process. Currently, cable selection involves choosing cables stored in various boxes with different specifications. Therefore, a system is needed to enhance the effectiveness and efficiency of the cable selection process. The approach used to address this issue involves developing a user interface for input, which is processed using a Raspberry Pi 4 connected to a servo motor that functions as the opener and closer of the cable storage boxes. The interface includes a login menu, a control menu, and a menu that allows users to add their own data. Additionally, the PCA9685 driver module is connected to the Raspberry Pi 4 to control 66 servo motors. The results of this research enhance the cable selection process by increasing its effectiveness and efficiency, as shown by a tool utilization effectiveness rate of 80.4%.